Comparative Evaluation of Hermetia Illucens Larvae Reared on Different Substrates: Effect on Growth (The Yield, Nutritional Properties and Bioconversion) Rate - Khasanah, Himmatul; Tyas, Iswahyuning; Kusbianto, Dwi Erwin; Jadmiko, Wildan; Muhlison, Wildan (Buletin Peternakan, 2024)
Media usage for Black Soldier Flies Larvae (BSFL) growth has not been standardized yet, and many research has tried to elucidate different substrates to produce optimal BSFL growth. This study aimed to analyse the effect of different media with different metabolizable energy and nutrient content, such as tofu waste (high metabolizable energy), Azolla microphylla (moderate metabolizable energy), and layer manure (low metabolizable energy), on the yield and nutritional properties of 19-d-old Black Soldier Fly Larvae (BSFL). We grew BSFL from egg to 19-d-old larvae and analysed the BSFL yields by total and individual weight. Nutritional properties were analysed by using proximate, including water content, ash, crude protein, crude fiber, and crude fat. The results showed that the growth media of BSFL on tofu waste, Azolla microphylla, and layer manure showed significant differences in total weight and individual weight (p<0.05). Tofu waste produced the highest total weight (280,75±4,99 g). The nutrient content (water, ash, crude protein, crude fat, and crude fiber) of BSFL grown on tofu waste is the best for yield production. Tofu waste also showed excellent performance in nutrient content except for the percentage of protein compared to Azolla, which was the highest among media, and tofu waste as a growth media for BSFL produced lower protein content. The fiber content of media might influence the protein content. In conclusion, we suggest using high metabolizable energy for BSFL growth media to obtain good yield and high nutrient properties.